"July Effect" Revisited: July Surgeries at Residency Training Programs are Associated with Equivalent Long-term Clinical Outcomes Following Lumbar Spondylolisthesis Surgery. Issue 12 (15th June 2021) - Chan, Andrew K.; Patel, Arati B.; Bisson, Erica F.; Bydon, Mohamad; Glassman, Steven D.; Foley, Kevin T.; Shaffrey, Christopher I.; Potts, Eric A.; Shaffrey, Mark E.; Coric, Domagoj; Knightly, John J.; Park, Paul; et al.
Abstract : Study Design: Retrospective analysis of a prospective registry. Objective: We utilized the Quality Outcomes Database (QOD) registry to investigate the "July Effect" at QOD spondylolisthesis module sites with residency trainees. Summary of Background Data: There is a paucity of investigation on the long-term outcomes following surgeries involving new trainees utilizing high-quality, prospectively collected data. Methods: This was an analysis of 608 patients who underwent single-segment surgery for grade 1 degenerative lumbar spondylolisthesis at 12 high-enrolling sites. Surgeries were classified as occurring in July or not in July (non-July). Outcomes collected included estimated blood loss, length of stay, operative time, discharge disposition, complications, reoperation and readmission rates, and patient-reported outcomes (Oswestry Disability Index [ODI], Numeric Rating Scale [NRS] Back Pain, NRS Leg Pain, EuroQol-5D [EQ-5D] and the North American Spine Society [NASS] Satisfaction Questionnaire). Propensity score-matched analyses were utilized to compare postoperative outcomes and complication rates between the July and non-July groups. Results: Three hundred seventy-one surgeries occurred at centers with a residency training program with 21 (5.7%) taking place in July. In propensity score-matched analyses, July surgeries were associated with longer operative times ( average treatment effect = 22.4 minutes longer, 95% confidence interval 0.9–449.0, P  = 0.041). Otherwise, July surgeries were not associated with significantly different outcomes for the remaining perioperative parameters (estimated blood loss, length of stay, discharge disposition, postoperative complications), overall reoperation rates, 3-month readmission rates, and 24-month ODI, NRS back pain, NRS leg pain, EQ-5D, and NASS satisfaction score ( P > 0.05, all comparisons). Conclusion: Although July surgeries were associated with longer operative times, there were no associations with other clinical outcomes compared to non-July surgeries following lumbar spondylolisthesis surgery. These findings may be due to the increased attending supervision and intraoperative education during the beginning of the academic year. There is no evidence that the influx of new trainees in July significantly affects long-term patient-centered outcomes. Level of Evidence: 3 Abstract : We utilized the Quality Outcomes Database (QOD) registry to investigate the "July Effect" at QOD spondylolisthesis module sites with residency trainees. Although July surgeries for grade 1 degenerative lumbar spondylolisthesis were associated with longer operative times, there were no associations with other clinical outcomes compared to non-July surgeries.